Approach to assessment of prerequisites for implementation of strategic directions of innovative development of industrial enterprises - Illiashenko, Sergiy; Illiashenko, Nataliia; Shypulina, Yuliia; Raiko, Diana; Bozhkova, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2021)
The present research substantiates the theorical and methodological foundations of quantitative assessment of the prerequisites for the implementation of strategic directions of innovative development of industrial enterprises under conditions of changing technological arrangement and the fourth industrial revolution. External and internal prerequisites for catching-up, leading and outstripping innovative development were determined and systematized. The two-step approach to assessing the sufficiency of prerequisites for the implementation of these directions was developed. It was proposed to assess external prerequisites according to the relative values of the indicators of the Global Innovation Index of the analyzed country, which take into account the highest and the lowest estimates of all countries Unlike existing approaches, the point-based score, rather than rating estimates of the indicators of countries are taken into account, which increases the assessment objectivity. The compliance of quantitative estimates with the levels of sufficiency of external prerequisites was determined using the Harrington Verbal-Numerical scale. It was proposed to assess internal prerequisites according to the author’s method of expert evaluations, which unlike existing ones, allows assessing the level of sufficiency of subsystems of the potential of innovative development of an enterprise. The two-step approach allows quantitative and comprehensive assessment of sufficiency of the prerequisites for the implementation of strategic directions of innovative development of industrial enterprises. It is possible to identify problems of prerequisites’ sufficiency, which allows their reasonable correction. The sufficiency of prerequisites for alternative directions of innovative development of machine-building enterprises was evaluated using the new approach and the best directions were chosen. The analysis time was reduced by 25–33 %, the accuracy of choice of directions and the effectiveness of their implementation strategies are increasing. The new approach improves strategic management of innovative development of industrial enterprises in the context of technological transformations